Development of a rehabilitation researcher survey of knowledge and interest in learning health systems research - Linda Resnik; Melissa A. Clark; Janet Freburger; Christine McDonough; Kathleen Poploski; Kristin Ressel; Margarite Whitten; Joel Stevans (Wiley, 2022)
Abstract Introduction LeaRRn, an NIH‐funded rehabilitation resource center, is dedicated to developing learning health systems (LHS) research competencies within the rehabilitation community. To appropriately target resources and training opportunities for rehabilitation researchers, we developed and pilot tested a survey based on AHRQ LHS research core competencies to assess the training needs of rehabilitation researchers interested in LHS research. Methods Survey items were developed by the investigative team and iteratively refined with the assistance of an expert panel using two rounds of content validation. Survey items addressed knowledge of, ability to apply, and interest in LHS research competencies. The survey was pre‐pilot tested with six rehabilitation professionals, refined again, and then pilot tested. Time to complete the survey was measured. Spearman correlations examined relationships between knowledge and ability. Results A 78‐item survey was pilot tested. Forty‐five individuals completed the pilot survey in full (71% female, 84% white, and 93% non‐Hispanic). Due to concerns about response burden (mean 15 minutes to complete) and strong correlation between "knowledge" and "ability" ratings (all rho >0.57), "ability" was dropped, resulting in a 55‐item survey assessing "knowledge" and "interest" in LHS research competencies. Conclusions We developed a survey of knowledge and interest in LHS research competencies for rehabilitation researchers. The resulting survey may be used to assess training needs and guide LHS research content development by educators, programs directors, and other initiatives within the rehabilitation research community.